IMPLIKASI PENGUNAAN MEDIA PEMBELAJARAN LCD PADA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 1 SIMBANG TAHUN PELAJARAN 2023/2024 - Ardianto, Ahmad Ari; -, Maryono; Sukawi, Zaenal (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2023)
This article aims to analyze the implications of using LCD learning media in Islamic Religious Education subjects at SD Negeri 1 Simbang for the 2023/2024 academic year. This field research is the result of descriptive qualitative research by collecting data from questionnaires, observations, interviews and documentation to then be analyzed qualitatively through the stages of data reduction, data presentation, and verification/conclusion drawing. The results of the study indicate that the use of LCD learning media in Islamic Religious Education subjects at Simbang 1 Public Elementary School has implications for increasing student interest in the material and they are more enthusiastic in participating in the learning process. Limitations are seen in the aspects of writing and student memory, in addition to the availability of LCDs that are not adequate for the number of classes, which are focuses that must be considered by the school in the future. These findings recommend that LCD media can be used for Islamic Religious Education learning at the elementary school level.